2006
DOI: 10.4161/cc.5.9.2710
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and Wanderings: Origins and Migrations in Asymmetrically Replicating Mitochondrial DNA

Abstract: Mammalian mitochondria maintain a small circular genome that encodes RNA and polypeptides that are essential for the generation of ATP through oxidative phosphorylation. The mechanism of replication of mammalian mitochondrial DNA (mtDNA) has recently been a topic of controversy. New evidence has led to a modified strand-displacement model that reconciles much of the current data. This revision stems from a new appreciation for alternative light-strand origins. We consider here some of the potential mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…A link between the displacement of the O L and the occurrence of gene rearrangements was suggested since alternative initiation sites could give instability to the replication mechanism, resulting in such rearrangements (Macey et al, 1997). Additionally, it has been shown that some tRNA in primate mitochondria can potentially function as an alternative O L , which may reconcile much of the controversy regarding the strand-displacement model (Brown and Clayton, 2006). The thermodynamic stability of the O L has also been correlated with developmental stability in reptiles ).…”
Section: Introductionmentioning
confidence: 93%
“…A link between the displacement of the O L and the occurrence of gene rearrangements was suggested since alternative initiation sites could give instability to the replication mechanism, resulting in such rearrangements (Macey et al, 1997). Additionally, it has been shown that some tRNA in primate mitochondria can potentially function as an alternative O L , which may reconcile much of the controversy regarding the strand-displacement model (Brown and Clayton, 2006). The thermodynamic stability of the O L has also been correlated with developmental stability in reptiles ).…”
Section: Introductionmentioning
confidence: 93%
“…Specifically, we have proposed that light-strand replication initiation can occur at various locations other than O L , as alternative light-strand origins ( alt O L ) (10,11). This alt O L modification of the standard model only requires, on occasion, a reduction in the asymmetry and a mechanism to initiate light-strand replication at locations other than O L .…”
mentioning
confidence: 99%
“…A recent study in which atomic force microscopy was used to examine mtDNA replicative intermediates in mouse liver was entirely consistent with the strand-displacement model, and did not show any evidence of the θ structures that would be predicted from the strand-coupled model 12 . The same study also provided evidence for alternative L-strand origins, and it was suggested that their presence, in addition to the propensity for branch migration in replicating DNA, might account for the patterns observed by 2-D gel electrophoresis that were interpreted as evidence for strand-coupled replication 13 .…”
mentioning
confidence: 77%